Components of the Engulfment Machinery Have Distinct Roles in Corpse Processing. - Tracy L Meehan; Tony F Joudi; Allison K Timmons; Jeffrey D Taylor; Corey S Habib; Jeanne S Peterson; Shanan Emmanuel; Nathalie C Franc; Kimberly McCall (PLoS ONE, 2016)
Billions of cells die in our bodies on a daily basis and are engulfed by phagocytes. Engulfment, or phagocytosis, can be broken down into five basic steps: attraction of the phagocyte, recognition of the dying cell, internalization, phagosome maturation, and acidification. In this study, we focus on the last two steps, which can collectively be considered corpse processing, in which the engulfed material is degraded. We use the Drosophila ovarian follicle cells as a model for engulfment of apoptotic cells by epithelial cells. We show that engulfed material is processed using the canonical corpse processing pathway involving the small GTPases Rab5 and Rab7. The phagocytic receptor Draper is present on the phagocytic cup and on nascent, phosphatidylinositol 3-phosphate (PI(3)P)- and Rab7-positive phagosomes, whereas integrins are maintained on the cell surface during engulfment. Due to the difference in subcellular localization, we investigated the role of Draper, integrins, and downstream signaling components in corpse processing. We found that some proteins were required for internalization only, while others had defects in corpse processing as well. This suggests that several of the core engulfment proteins are required for distinct steps of engulfment. We also performed double mutant analysis and found that combined loss of draper and αPS3 still resulted in a small number of engulfed vesicles. Therefore, we investigated another known engulfment receptor, Crq. We found that loss of all three receptors did not inhibit engulfment any further, suggesting that Crq does not play a role in engulfment by the follicle cells. A more complete understanding of how the engulfment and corpse processing machinery interact may enable better understanding and treatment of diseases associated with defects in engulfment by epithelial cells.